Adsorção-dessorção de partículas neutras em sistemas com superfícies não-idênticas - Guimarães, Veridiana Garcia (2015)
The adsorption and diffusion phenomena at solid-liquid interfaces has been investigated, since their findings, in several contexts due to wide occurrence in nature. In this work, a confined system filled with a liquid that contains dispersed neutral particles is theoretically studied in two different ways. One of them is investigated when the limiting surfaces presents identical dynamics. The other one is investigated for the case where surfaces present different parameters and/or different mechanisms for adsorption-desorption phenomena by considering different non-singular kernels in the kinetic equations at the walls, where the suitable choice of the kernel can account for the relative importance of physisorption or chemisorption. We find that even a small difference in the adsorptiondesorption rate of one surface (relative to the other) can drastically affect the behavior of the whole system. The surface and bulk densities and the dispersion are calculated when several scenarios are considered. To finish, we analyse the diffusive regimes resulting due to presence of the different surfaces. Anomalous-like behavior was found. The approach described here is closely related to experimental situations, and can be applied in several contexts such as dielectric relaxation, diffusion-controlled relaxation in liquids, liquid crystals, and amorphous polymers.